Participation and innovation, the keys to rural development: the case of rural medellin (2011)
The challenge of rural development in the Municipality of Medellin has to do with a political decision to assess processes based on participation and innovation in rural communities. The authorities have the opportunity to establish a territory in order to guarantee stability and consolidation of the populations considering their many activities when the districts are threatened by rampant urban sprawl. The opportunity exists to rebuild civil society in the territory based on cultural identity and to build new spaces without exclusion.